Grantville Gazette. IX. - Flint, Eric; Boyes, Walt; Ward, Joy (Ring of fire (Riverdale, N.Y.), 2022)
"When a cosmic disturbance hurls your town from twentieth-century West Virginia back to seventeenth-century Europe--and into the middle of the Thirty Years War--you have to adapt to survive. And the natives of that time period, faced with American technology and politics, need to be equally adaptable. Here's a generous helping of more stories of Grantville, the American town lost in time, and its impact on the people and societies of a tumultuous age"--Provided by publisher.